A retrospective analysis of factors associated with the length of hospital stay in COVID-19 patients treated with Nirmatrelvir / Ritonavir - Zheng, Jiantao; Hong, Wencong; Zhou, Chanjuan; Hong, Donghuang; Yan, Hong; Shen, Yanghui (Frontiers in Pharmacology, 2023)
Objectives: This study reviewed factors influencing the length of hospital stay in adult in-patients with confirmed Coronavirus disease (Covid-19) who were treated with Nirmatrelvir / Ritonavir. Methods: We did a retrospective analysis of data from a cohort of in-patients with confirmed diagnosis of Omicron variant of SARS-CoV-2 infection who were treated with Nirmatrelvir / Ritonavir. We included patients who were treated from 13th March 2022 to 6th May 2022 in various in-patient treatment units in Quanzhou, Fujian Province, China. The primary study outcome was the length of hospital stay. Secondary study outcome was viral elimination defined as negative for ORF1ab and N genes (cycle threshold (Ct) value ≥ 35 in real-time PCR), according to local guidelines. Hazard ratios (HR) of event outcomes were analyzed using Multivariate Cox regression models. Results: We studied 31 in-patients with high risk for severe COVID-19 who were treated with Nirmatrelvir / Ritonavir. We found that in-patients with shorter length of hospital stay (≤ 17 days) were mostly females with lower body mass index (BMI) and Charlson Comorbidity Index (CCI) index. Their treatment regimen with Nirmatrelvir / Ritonavir was started within 5 days of diagnosis (P < 0.05). Multivariate Cox regression indicated that in-patients starting treatment of Nirmatrelvir / Ritonavir within 5 days had a shorter length of hospital stay (HR 3.573, P = 0.004) and had a faster clearance of viral load (HR 2.755, P=0.043). Conclusion: This study assumes relevance during the Omicron BA.2 epidemic as our findings suggest that early treatment with Nirmatrelvir / Ritonavir within 5 days of diagnosis (≤ 5days) was highly effective in shortening the length of hospital stay and faster viral load clearance.